Mapping soil carbon, particle-size fractions, and water retention in tropical dry forest in Brazil - Vasques, Gustavo Mattos; Coelho, Maurício Rizzato; Dart, Ricardo Oliveira; Oliveira, Ronaldo Pereira; Teixeira, Wenceslau Geraldes (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to compare ordinary kriging with regression kriging to map soil properties at different depths in a tropical dry forest area in Brazil. The 11 soil properties evaluated were: organic carbon content and stock; bulk density; clay, sand, and silt contents; cation exchange capacity; pH; water retention at field capacity and at permanent wilting point; and available water. Samples were taken from 327 sites at 0.0–0.10, 0.10–0.20, and 0.20–0.40-m depths, in a tropical dry forest area of 102 km2. Stepwise linear regression models for particle-size fractions and water retention properties had the best fit. Relief and parent material covariates were selected in 31 of the 33 models (11 properties at three depths) and vegetation covariates in 29 models. Based on external validation, ordinary kriging obtained higher accuracy for 21 out of 33 property x depth combinations, indicating that the inclusion of a linear trend model before kriging does not necessarily improve predictions. Therefore, for similar studies, the geostatistical methods employed should be compared on a case-by-case basis.